Preparation method of fuel cell gas diffusion layer with gradient microporous layer

By forming a gradient microporous layer structure in the fuel cell gas diffusion layer, the problem of poor water and gas management capabilities in the prior art is solved, and the performance and water and gas management capabilities of the fuel cell are significantly improved.

CN119764465AActive Publication Date: 2025-04-04HARBIN INST OF TECH

Patent Information

Application Number
CN202411748915.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing gradient gas diffusion layer has poor water and gas management capabilities, which leads to fuel cells being prone to flooding under long-term operation and high current density conditions, affecting battery performance.

Method used

The slurry prepared through different dispersions is coated on the surface of hydrophobic carbon paper in sequence to form a multi-layer microporous layer structure, establish a gradient microporous layer pore structure, and improve the porosity and water gas management capabilities of the gas diffusion layer.

Benefits of technology

The performance of fuel cells has been significantly improved, including improving peak power density and improving water and gas management capabilities. Compared with the applications of commercial gas diffusion layers and traditional gradient-free homogeneous gas diffusion layers, the performance has been improved by 21.99% to 34.78%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764465A_ABST
    Figure CN119764465A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a fuel cell gas diffusion layer with a gradient microporous layer, relates to a preparation method of a fuel cell gas diffusion layer, and aims to solve the technical problem of poor water-gas management capability of the existing gradient gas diffusion layer. The preparation method comprises the following steps: preparing dispersion liquid according to different volume fractions of the alcohol solvent, and adding the carbon powder and the water repellent agent into the dispersion liquid to obtain different slurries; the preparation method comprises the following steps: preparing a slurry from a Dongli commercial gas diffusion layer, sequentially coating the surface of hydrophobic carbon paper with the slurry to obtain a gas diffusion layer with a multi-layer microporous layer structure, forming a gradient microporous layer pore channel structure in the longitudinal direction, and ensuring that the porosity of the gas diffusion layer is 82.97%. The peak power density of the fuel cell provided by the invention is 1659-1833 mW.cm <-2 >, which is improved by 21.99%-34.78% compared with that of a fuel cell using a Dongli commercial gas diffusion layer, and the fuel cell can be used in the field of fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a fuel cell gas diffusion layer, and belongs to the field of new energy battery materials. Background Art

[0002] As a clean energy with great potential, hydrogen energy is widely recognized and increasingly supported. Hydrogen fuel cells are a sustainable energy conversion system, among which proton exchange membrane fuel cells are the most widely used. The advantages of high energy conversion efficiency and long operating life make it one of the most promising devices to replace traditional energy conversion devices. Proton exchange membrane fuel cells are composed of bipolar plates, proton exchange membranes, catalyst layers and gas diffusion layers. The gas diffusion layer is one of the most important components of proton exchange membrane fuel cells. It is composed of a substrate layer and a microporous layer. During the operation of the battery, it supports the catalyst layer and provides gas channels, ion channels and drainage channels for electrode reactions.

[0003] The water vapor transmission mechanism inside the gas diffusion layer is complex, and the gas diffusion layer will be flooded when operating for a long time and under high current density conditions. The gas diffusion layer can effectively improve the gas transmission and water management capabilities of the gas diffusion layer by gradient design of the pore structure of the microporous layer, and timely discharge the liquid water accumulated at the electrode interface to improve the performance of the fuel cell. However, the current preparation technology for gradient gas diffusion layers mostly uses carbon powder materials of different types and particle sizes to construct gradient microporous layers, and such microporous layers have poor water vapor management capabilities. Summary of the invention

[0004] The present invention aims to solve the technical problem of poor water vapor management ability of the existing gradient gas diffusion layer, and provides a method for preparing a fuel cell gas diffusion layer with a gradient microporous layer. The present invention prepares different slurries with different dispersions and sequentially coats them on the surface of hydrophobic carbon paper to obtain a gas diffusion layer with a multi-layer microporous layer structure, forms a gradient microporous layer pore structure in the longitudinal direction, improves the porosity of the gas diffusion layer, and the performance of the fuel cell using the gas diffusion layer is greatly improved compared with the performance of the fuel cell using the commercial gas diffusion layer and the traditional non-gradient uniform gas diffusion layer.

[0005] The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer of the present invention is carried out according to the following steps:

[0006] 1. Preparation of carbon paper substrate layer: soaking raw carbon paper in ethanol solution, ultrasonic cleaning for 30 minutes, and vacuum drying; preparing polytetrafluoroethylene (PTFE) emulsion, soaking the dried raw carbon paper in the PTFE emulsion, and sintering at high temperature in an inert atmosphere to obtain a carbon paper substrate layer containing polytetrafluoroethylene;

[0007] 2. Preparation of slurry of different dispersions:

[0008] According to the volume fraction V1 of the alcohol solvent being 70% to 95%, the alcohol solvent and water are uniformly mixed to obtain a dispersion A;

[0009] According to the volume fraction V2 of the alcohol solvent being 5% to 30%, the alcohol solvent and water are uniformly mixed to obtain a dispersion B;

[0010] Add carbon powder and hydrophobic agent into dispersion A at a mass ratio of (2.3-4):1, stir evenly, and obtain slurry A;

[0011] Add carbon powder and hydrophobic agent into dispersion B at a mass ratio of (2.3-4):1, stir evenly, and obtain slurry B;

[0012] The types of carbon powder and hydrophobic agent in slurry A and slurry B are the same;

[0013] 3. Preparation of microporous layer: Spray the slurry A prepared in step 2 on the carbon paper base layer treated in step 1 by ultrasonic spraying to obtain microporous layer A. After the microporous layer A is dried, continue to spray slurry B on the microporous layer A to obtain microporous layer B. After spraying, sinter at high temperature in an inert atmosphere to obtain a fuel cell gas diffusion layer with a gradient microporous layer.

[0014] Furthermore, the vacuum drying temperature in step 1 is 60-90°C.

[0015] Furthermore, the mass concentration of the PTFE emulsion described in step one is 10% to 20%.

[0016] Furthermore, the sintering temperature in step 1 is 300-400° C., and the sintering time is 20-60 min.

[0017] Furthermore, the alcohol solvent in step 2 is one or more of ethanol, isopropanol and n-butanol.

[0018] Furthermore, the carbon powder in step 2 is one or more of Vulcan XC-72, acetylene black, carbon nanotubes, and graphite powder.

[0019] Furthermore, the hydrophobic agent described in step 2 is one or a mixture of polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), polychlorotrifluoroethylene (PCTFE), tetrafluoroethylene-ethylene copolymer (ETFE) and polyvinylidene fluoride (PVDF).

[0020] Furthermore, in step 2, the relationship between the volume fraction V1 of the alcohol solvent in the dispersion A and the volume fraction V2 of the alcohol solvent in the dispersion B is V1=90%, V2=10%; V1=80%, V2=20%; V1=70%, V2=30%. This design ensures that the slurry A and slurry B have a significant difference in the alcohol solvent content.

[0021] Furthermore, in step 3, when the slurry prepared in step 2 is ultrasonically sprayed, the sprayed solid phase material loading of microporous layer A and microporous layer B is 0.5-1.0 mg / cm 2 .

[0022] Furthermore, in step 3, the drying temperature of the microporous layer A is 70 to 85° C., and the drying time is 5 to 15 min;

[0023] Furthermore, in step three, the inert atmosphere is Ar or N2.

[0024] Furthermore, in step three, the high temperature sintering has a sintering temperature of 250-400° C. and a sintering time of 20-60 min.

[0025] The beneficial effects of the present invention compared to the prior art are:

[0026] (1) In the present invention, the water-to-alcohol ratios in the dispersions of slurry A and slurry B are different, so there are obvious differences in the drying rates of the slurries. Different evaporation rates will produce differentiated primary pores between carbon powder particles. In addition, water and alcohol have different affinities for carbon powder and hydrophobic agent, and the dispersion effects of carbon powder and hydrophobic agent in dispersions with different water-to-alcohol ratios are significantly different. Under the combined action of the hydrophobic agent and the dispersion, the carbon powder particles are subjected to different forces to form differentiated secondary pores. Spraying slurries with different water-to-alcohol ratios in sequence will form different pore structures, and a gas diffusion layer with a gradient pore structure will be formed in the longitudinal direction of the gas diffusion layer.

[0027] (2) The gas diffusion layer with a gradient pore structure prepared by the present invention rationally regulates the pore distribution of the microporous layer, increases the porosity of the gas diffusion layer, reduces the resistivity, and effectively improves the water vapor management capability. The gas diffusion layer can improve the battery performance when applied to a fuel cell. The fuel cell prepared by using the fuel cell gas diffusion layer with a gradient microporous layer of the present invention and the Toray commercial gas diffusion layer under the same conditions has a peak power density of 1659 to 1833 mW·cm -2 , which is 21.99% to 34.78% higher than the application of Toray's commercial gas diffusion layer in fuel cells, and has application prospects.

[0028] (3) The method and reagents used in the present invention are simple, the manufacturing process cost is low, the time is short, the economic benefit is high, and there is good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a surface SEM image of a fuel cell gas diffusion layer having a gradient microporous layer prepared in Example 1;

[0030] Figure 2 is a cross-sectional SEM image of a fuel cell gas diffusion layer having a gradient microporous layer prepared in Example 1;

[0031] Figure 3 is a surface SEM image of a fuel cell gas diffusion layer having a gradient microporous layer prepared in Example 2;

[0032] Figure 4 It is a comparison diagram of the porosity of the gas diffusion layer of the battery of Example 1 and Comparative Example 1 and Comparative Example 2;

[0033] Figure 5 It is a comparison diagram of contact angles of battery gas diffusion layers of Example 1, Comparative Example 1, and Comparative Example 2;

[0034] Figure 6 It is a comparison chart of the resistivity of the gas diffusion layer of the battery of Example 1, Comparative Example 1, Comparative Example 2, and the commercial TGP-H-060 gas diffusion layer;

[0035] Figure 7 This is a comparison chart of fuel cell performance using Example 1, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer;

[0036] Figure 8 It is a comparison chart of fuel cell performance using Example 2, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments so that those skilled in the art can better understand the present invention and implement it. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments do not limit the content and protection scope of the present invention. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0038] Embodiment 1: The preparation method of the fuel cell gas diffusion layer having a gradient microporous layer of this embodiment is carried out according to the following steps:

[0039] 1. Preparation of carbon paper substrate: commercial TGP-H-060 raw carbon paper was cut into 2.25×2.25 cm squares, immersed in ethanol solution, ultrasonically cleaned for 30 min, and then dried in a vacuum drying oven at 60°C for 8 h; 12.5 g of 60% PTFE emulsion and 37.5 g of deionized water were stirred and mixed, and the dried raw carbon paper was immersed in the mixed solution for 2 min and then taken out, and heated to 350°C at 2°C / min in an Ar atmosphere and maintained for 60 min, and then naturally cooled to room temperature to obtain a carbon paper substrate containing PTFE;

[0040] 2. Preparation of slurry of different dispersions:

[0041] 18 mL of isopropanol and 2 mL of deionized water were mixed and stirred for 10 min to obtain dispersion A;

[0042] Mix 2 mL of isopropanol and 18 mL of deionized water and stir for 10 min to obtain dispersion B;

[0043] 0.143 g of 60% PTFE emulsion and 0.2 g of Vulcan XC-72 carbon powder were added to dispersion A, and sheared and dispersed for 30 minutes using a high shear emulsifier to obtain slurry A.

[0044] 0.143 g of 60% PTFE emulsion and 0.2 g of Vulcan XC-72 carbon powder were added to dispersion B, and sheared and dispersed for 30 minutes using a high shear emulsifier to obtain slurry B;

[0045] 3. Preparation of microporous layer: The slurry A prepared in step 2 is sprayed on the carbon paper substrate layer treated in step 1 by ultrasonic spraying, and the sprayed solid phase is controlled to be 0.7 mg / cm 2 , and dried at 75°C for 5 min to obtain microporous layer A; slurry B was sprayed on microporous layer A, and the spraying loading was controlled to be 0.7 mg / cm 2 , and dried at 75°C for 5 minutes to obtain a microporous layer B. After spraying, it was placed in a furnace and heated to 350°C at 5°C / min in an Ar atmosphere and maintained for 30 minutes, then naturally cooled to room temperature to obtain a fuel cell gas diffusion layer with a gradient microporous layer.

[0046] Embodiment 2: The preparation method of the fuel cell gas diffusion layer having a gradient microporous layer of this embodiment is carried out according to the following steps:

[0047] 1. Preparation of a hydrophobic base layer: This step is the same as the method in step 1 of Example 1;

[0048] 2. Preparation of microporous layer slurry:

[0049] Mix 24 mL of isopropanol and 6 mL of deionized water and stir for 10 min to obtain dispersion A;

[0050] Mix 6 mL of isopropanol and 24 mL of deionized water and stir for 10 min to obtain dispersion B;

[0051] 0.215 g of 60% PTFE emulsion and 0.3 g of Vulcan XC-72 carbon powder were added to dispersion A, and sheared and dispersed for 30 minutes using a high shear emulsifier to obtain slurry A.

[0052] 0.215 g of 60% PTFE emulsion and 0.3 g of Vulcan XC-72 carbon powder were added to dispersion B, and sheared and dispersed for 30 minutes using a high shear emulsifier to obtain slurry B;

[0053] 3. Preparation of gas diffusion layer: This step is the same as the method in step 3 of Example 1.

[0054] Comparative Example 1: The preparation method of the gas diffusion layer of this comparative example is carried out according to the following steps:

[0055] 1. Preparation of hydrophobic base layer: This step is the same as the method in step 1 of Example 1;

[0056] 2. Preparation of microporous layer slurry: 18 mL of isopropanol and 2 mL of deionized water were mixed and stirred for 10 min to obtain dispersion A; 0.143 g of 60% PTFE emulsion and 0.2 g of Vulcan XC-72 carbon powder were added to dispersion A, and sheared and dispersed for 30 min using a high shear emulsifier to obtain slurry A;

[0057] 3. Preparation of gas diffusion layer: Use ultrasonic spraying method to evenly spray slurry A on the hydrophobic treated carbon paper substrate layer, and control the spraying load to 1.4 mg / cm 2 , and dried at 75°C for 5 minutes, then placed in a furnace, heated to 350°C at 5°C / min in an Ar atmosphere and maintained for 30 minutes, and naturally cooled to room temperature to obtain a gas diffusion layer with a gradient-free uniform microporous layer.

[0058] Comparative Example 2: The preparation method of the gas diffusion layer of this comparative example is carried out according to the following steps:

[0059] 1. Preparation of hydrophobic base layer: This step is the same as the method in step 1 of Example 1;

[0060] 2. Preparation of microporous layer slurry: 24 mL of isopropanol and 6 mL of deionized water were mixed and stirred for 10 min to obtain dispersion A; 0.215 g of 60% PTFE emulsion and 0.3 g of Vulcan XC-72 carbon powder were added to dispersion A, and sheared and dispersed for 30 min using a high shear emulsifier to obtain slurry A;

[0061] 3. Preparation of gas diffusion layer: Use ultrasonic spraying method to evenly spray slurry A on the hydrophobic treated carbon paper substrate layer, and control the spraying load to 1.4 mg / cm 2 , and dried at 75°C for 5 minutes, then placed in a furnace, heated to 350°C at 5°C / min in an Ar atmosphere and maintained for 30 minutes, and naturally cooled to room temperature to obtain a gas diffusion layer with a gradient-free uniform microporous layer.

[0062] The surface morphology of the fuel cell gas diffusion layer with a gradient microporous layer prepared in Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that micropores and mesopores with different pore sizes are alternately distributed on the surface.

[0063] Figure 2 is a scanning electron microscope photograph of a cross section of a fuel cell gas diffusion layer having a gradient microporous layer prepared in Example 1. Figure 2 It can be seen that there are two microporous layers on the surface of the carbon paper substrate, the upper layer has a large pore size, and the lower layer has a small pore size, forming a gradient. This is formed by sequentially spraying slurries prepared from dispersions with different water-to-alcohol ratios onto the carbon paper substrate. There are obvious differences in the drying rates of dispersions with different water-to-alcohol ratios, and different evaporation rates will produce differentiated primary pores between carbon powder particles; in addition, water and alcohol have different affinities for carbon powder and hydrophobic agents, and the dispersion effects of carbon powder and hydrophobic agents in dispersions with different water-to-alcohol ratios are significantly different. Under the combined action of the hydrophobic agent and the dispersion, the carbon powder particles are subjected to different forces to form differentiated secondary pores. Sequentially spraying slurries with different water-to-alcohol ratios will form a gas diffusion layer with a gradient pore structure in the longitudinal direction of the gas diffusion layer.

[0064] The surface morphology of the fuel cell gas diffusion layer with a gradient microporous layer prepared in Example 2 is as follows: Figure 3 As shown, from Figure 3 It can be seen that there are a large number of small holes distributed on the surface, and the pore diameter is slightly smaller than that of Example 1.

[0065] Figure 4 is a comparison chart of the porosity of Example 1, Comparative Example 1 and Comparative Example 2. Figure 4It can be seen that the porosity of the fuel cell gas diffusion layer with a gradient microporous layer of Example 1 is 82.97%, and the porosity of the gas diffusion layer prepared in Comparative Example 1 is 56.54%. The preparation process of Comparative Example 1 is a traditional ultrasonic spraying method, and the prepared gas diffusion layer has only one uniform microporous layer. Compared with the gas diffusion layer with a uniform non-gradient microporous layer of Comparative Example 1, the porosity of the fuel cell gas diffusion layer with a gradient microporous layer of Example 1 is increased by 26%, and the porosity is increased by 16% relative to the gas diffusion layer with a comparative uniform non-gradient microporous layer prepared in Comparative Example 2. The fuel cell gas diffusion layer with a gradient microporous layer prepared in Example 1 has more water vapor transmission channels.

[0066] Figure 5 is a contact angle comparison diagram of Example 1, Comparative Example 1 and Comparative Example 2, Figure 5 It shows that the contact angle of the gas diffusion layer prepared in Example 1 is 149.8°, which is larger than the contact angle of the gas diffusion layer of the uniform non-gradient microporous layer prepared in Comparative Example 1 and Comparative Example 2, indicating that the hydrophobicity of the surface of the diffusion layer prepared in Example 1 is stronger. When applied to fuel cells, the liquid water generated on the surface of the microporous layer during the electrochemical reaction process can be removed more quickly, effectively suppressing the "flooding" phenomenon under high current density.

[0067] Figure 6 is a comparison chart of the resistivity of Example 1, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer. Figure 6 It can be seen that the electrical conductivity of the gas diffusion layer of Experimental Example 1 is 5.9 mΩ·cm, which is 0.21 mΩ·cm lower than that of the diffusion layer of Comparative Example 1, 0.61 mΩ·cm lower than that of the diffusion layer of Comparative Example 2, and 3.72 mΩ·cm lower than that of Toray's commercial gas diffusion layer. In comparison, the gas diffusion layer prepared in Example 1 has a lower resistivity and improves the electron conduction capability.

[0068] Example 1, Example 2, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer were applied to the battery, and the cathode Pt catalyst loading was 0.3 mg / cm 2 , the anode Pt catalyst loading is 0.1 mg / cm 2 A proton exchange membrane was used, commercial TGP-H-060 was used as the anode gas diffusion layer, and fuel cells were assembled using Example 1, Example 2, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer as the cathode gas diffusion layer. The anode and cathode test gases were air (flow rate 2 ml / min) and hydrogen (flow rate 0.5 ml / min), and the battery polarization curve and power density performance tests were performed. The test voltage was scanned from 1.0 V to 0.2 V, and the scan rate was 0.05 V / min.

[0069] Figure 7 The fuel cell performance comparison chart of Example 1, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer is shown in Figure 1. Figure 7 It can be seen that the peak power density of the fuel cell prepared with the gas diffusion layer of Example 1 is 1833 mW·cm -2 The peak power density value is increased by 46.52% compared with the fuel cell prepared with the gas diffusion layer of Comparative Example 1, by 64.99% compared with the fuel cell prepared with the gas diffusion layer of Comparative Example 2, and by 34.78% compared with the fuel cell using the commercial TGP-H-060 gas diffusion layer.

[0070] Figure 8 The fuel cell performance comparison chart of Example 2, Comparative Example 1, Comparative Example 2, and commercial TGP-H-060 gas diffusion layer is shown in FIG. Figure 8 It can be seen that the peak power density of the fuel cell prepared with the gas diffusion layer of Example 2 is 1659 mW·cm -2 The peak power density value is increased by 32.61% compared with the fuel cell prepared with the gas diffusion layer of Comparative Example 1, by 49.32% compared with the fuel cell prepared with the gas diffusion layer of Comparative Example 2, and by 21.99% compared with the fuel cell prepared with the commercial TGP-H-060 gas diffusion layer.

[0071] The fuel cell gas diffusion layer with a gradient microporous layer of the present invention is a carbon paper substrate layer with two microporous layers arranged on the surface, the upper layer has a large pore size, and the lower layer has a small pore size, forming a gradient distribution, with stronger hydrophobicity, improved water vapor management capabilities, and thus improved fuel cell performance.

Claims

1. A method for preparing a fuel cell gas diffusion layer having a gradient microporous layer, characterized in that The method proceeds as follows:

1. Preparation of carbon paper substrate layer: soaking raw carbon paper in ethanol solution, ultrasonic cleaning for 30 minutes, and vacuum drying; preparing polytetrafluoroethylene emulsion, soaking the dried raw carbon paper in PTFE emulsion, and sintering at high temperature in an inert atmosphere to obtain a carbon paper substrate layer containing polytetrafluoroethylene; 2. Preparation of slurry of different dispersions: According to the volume fraction V1 of the alcohol solvent being 70% to 95%, the alcohol solvent and water are uniformly mixed to obtain a dispersion A; According to the volume fraction of the alcohol solvent V2 = 5% to 30%, the alcohol solvent and water are mixed uniformly to obtain a dispersion B; Add carbon powder and hydrophobic agent into dispersion A at a mass ratio of (2.3-4):1, stir evenly, and obtain slurry A; Add carbon powder and hydrophobic agent into dispersion B at a mass ratio of (2.3-4):1, stir evenly, and obtain slurry B; The types of carbon powder and hydrophobic agent in slurry A and slurry B are the same; 3. Preparation of microporous layer: Spray the slurry A prepared in step 2 on the carbon paper base layer treated in step 1 by ultrasonic spraying to obtain microporous layer A. After the microporous layer A is dried, continue to spray slurry B on the microporous layer A to obtain microporous layer B. After spraying, sinter at high temperature in an inert atmosphere to obtain a fuel cell gas diffusion layer with a gradient microporous layer.

2. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1, characterized in that: The vacuum drying temperature in step 1 is 60-90°C.

3. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: The mass percentage concentration of the PTFE emulsion described in step one is 10% to 20%.

4. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: The sintering temperature in step 1 is 300-400° C., and the sintering time is 20-60 min.

5. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: The alcohol solvent described in step 2 is one or more of ethanol, isopropanol and n-butanol.

6. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: The carbon powder described in step 2 is one or more of Vulcan XC-72, acetylene black, carbon nanotubes, and graphite powder.

7. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: The hydrophobic agent described in step 2 is one or a mixture of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polychlorotrifluoroethylene, tetrafluoroethylene-ethylene copolymer and polyvinylidene fluoride.

8. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: In step 3, when the slurry prepared in step 2 is ultrasonically sprayed, the sprayed solid phase material loading of microporous layer A and microporous layer B is 0.5-1.0 mg / cm 2 .

9. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: In step 3, the drying temperature of the microporous layer A is 70-85° C., and the drying time is 5-15 minutes.

10. The method for preparing a fuel cell gas diffusion layer having a gradient microporous layer according to claim 1 or 2, characterized in that: In step three, the high temperature sintering has a sintering temperature of 250-400° C. and a sintering time of 20-60 min.

Citation Information

Patent Citations

  • Preparation method for anode microporous layer of dimethyl ether fuel cell

    CN106960972A

  • Preparation method of double-layer microporous layer-type gas diffusion layer

    CN111009666A

  • Fuel cell gas diffusion layer and preparation method thereof

    CN114267845A

  • Preparation method and application of ordered multi-layer cathode catalyst layer membrane electrode

    CN114583187A

Cited By

  • Integrated three-dimensional labyrinth pore gas diffusion layer and preparation method thereof

    CN121307056A